Analisis Buku Al-‘Arabiyyah Baina Yadaik Jilid I - Riza Pahlevi (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
Learning the Arabic language is insaperable from the role of the textbook as learning materials. Inside are the shoe material arranged systematically. In the process of drafting the text of the book as well as the formulation of the shoe material in it must go through a thorough review so that the liquid quality handbook. Because a quality book is will be highly influential in supporting the learning procces, whether a student or a teacher. Among some of the textbooks that are used as the main material, one of wich was Al-Arabiya Baina Yadaik vol. I used for beginner learners. This paper tries to analyze the material in the presented in the book Al-Arabiya Baina Yadaik vol. I annalytical approach with the material of the textbook.